2017
DOI: 10.1002/brb3.672
|View full text |Cite
|
Sign up to set email alerts
|

Valence and magnitude ambiguity in feedback processing

Abstract: BackgroundOutcome feedback which indicates behavioral consequences are crucial for reinforcement learning and environmental adaptation. Nevertheless, outcome information in daily life is often totally or partially ambiguous. Studying how people interpret this kind of information would provide important knowledge about the human evaluative system.MethodsThis study concentrates on the neural processing of partially ambiguous feedback, that is, either its valence or magnitude is unknown to participants. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 81 publications
4
19
0
Order By: Relevance
“…This suggests that when feedback did not carry any valuable information regarding action value, it took longer to update this event than when a clear value could readily be extracted based on it. Interestingly, in both groups, this uninformative feedback also elicited an FRN component prior to the delayed P3, resembling that elicited for the negative feedback, similar to what Gu et al (2017) previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that when feedback did not carry any valuable information regarding action value, it took longer to update this event than when a clear value could readily be extracted based on it. Interestingly, in both groups, this uninformative feedback also elicited an FRN component prior to the delayed P3, resembling that elicited for the negative feedback, similar to what Gu et al (2017) previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…The electrodes used in data analysis on the P3 were Cz, CPz, and Pz influence of self-affirmation on behavioral response, which is not rare when the feedback probability was controlled (Gu, Ge, et al, 2010;Gu, Huang, et al, 2010). However, we replicated the main findings of past ERP studies on decisionmaking: first, the FRN showed similar amplitude in response to ambiguous and negative feedback in the control group (Becker, Nitsch, Miltner, & Straube, 2014;Gu et al, 2017;Holroyd, Hajcak, & Larsen, 2006); second, the P3 is larger in response to large magnitude feedback over small and to positive feedback compared to negative and ambiguous feedback (Gu, Ge, et al, 2010;Gu, Lei, et al, 2011). These findings suggest that using the gambling task with EEG recording was successful.…”
Section: Discussionsupporting
confidence: 76%
“…However, losses need not necessarily represent expectancy violation, such as cases where the player does not yet have a reliable understanding of their opponent's dominant strategy. The current data would also seem to suggest that it is only unambiguously negative outcomes (losses) rather than ambiguously negative outcomes (draws) that puncture the failure-faster link (see Gu, Feng, Broster, Yuan, Xu & Luo, 2017, for further discussion). Future research incorporating individual differences in empathy, locus of control, personal understanding of luckskill balance, accuracy of meta-cognition regarding one's own performance, and the use of early neural responses to predict eventual behavioural outcomes will serve to further identify the conditions under which one becomes more or less impulsive as a function of outcome.…”
Section: Discussionmentioning
confidence: 71%